Decolourisation of Dyeing Effluent by the Fungal Biomass in a Fluidized Bed Reactor - Balaji, K (International Journal of Pharmaceutical & Biological Archive, 2012)
Decolourisation of Dyeing Effluent by the Fungal Biomass in a Fluidized Bed Reactor